2017
DOI: 10.1007/5584_2017_126
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure and Kidney Disease

Abstract: Kidney disease is commonly found in heart failure (HF) patients. They share many risk factors and common pathophysiological pathways which often lead to mutual dysfunction. Both haemodynamic and non-haemodynamic mechanisms are involved in the development of renal impairment in heart failure patients. Moreover, the presence of a chronic kidney disease is a significant independent predictor of worse outcome in chronic as well as in acute decompensated HF. As a consequence, an accurate evaluation of renal functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 131 publications
0
18
0
1
Order By: Relevance
“…Renal dysfunction is becoming a common abnormality in cardiovascular diseases and its burden may be often seen in HFrEF patients [8][9]. In our study, patients with chronic kidney disease with eGFR <60ml/min/1.73 m2 had more advanced age in comparison to other 2 groups.…”
Section: Discussionmentioning
confidence: 51%
“…Renal dysfunction is becoming a common abnormality in cardiovascular diseases and its burden may be often seen in HFrEF patients [8][9]. In our study, patients with chronic kidney disease with eGFR <60ml/min/1.73 m2 had more advanced age in comparison to other 2 groups.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies indicated that pressure and volume overload were the major contributors to LVH in CKD. However, LVH still develops even after mitigating these 2 factors [63]. Recent data prefer to pay more attention on the role of Klotho in CKD-induced LVH.…”
Section: The Role Of Klotho In Left Ventricular Hypertrophymentioning
confidence: 99%
“…As terapias atuais recomendadas para ICC demonstraram melhorar a qualidade de vida e a sobrevivência dos pacientes, entretanto podem comprometer a função renal (Grande et al, 2017).…”
Section: Tratamento Da Scr Tipo IIunclassified